Perlindungan Hukum bagi Petugas Pemasyarakatan dalam Menghadapi Risiko Kekerasan dan Gangguan Keamanan pada Rumah Tahanan Negara Kelas IIB Kraksaan - Mohammad Alfarizi; Muhammad Dluha; Ach. Syamsul Askandar (Jurnal Hukum Lex Generalis, 2026)
This research discusses the legal protection for correctional officers in facing the risks of violence and security disturbances at the Class IIB State Detention Center of Kraksaan. The study is motivated by the high potential for physical and psychological threats faced by officers while performing security and rehabilitation duties for inmates. This research employs an empirical legal method with a qualitative approach. The findings indicate that, normatively, legal protection for correctional officers has been regulated under Law Number 22 of 2022 concerning Corrections; however, its implementation has not been optimal. This is due to limitations in human resources, facilities and infrastructure and suboptimal institutional support. Therefore, strengthening policies and legal protection systems is essential to ensure safety and legal certainty for correctional officers.